Next generation sequencing (NGS): a golden tool in forensic toolkit - Sanaa M. Aly; Dalia M. Sabri (Archives of Forensic Medicine and Criminology, 2016)
The DNA analysis is a cornerstone in contemporary forensic sciences. DNA sequencing technologies are powerful tools that enrich molecular sciences in the past based on Sanger sequencing and continue to glowing these sciences based on Next generation sequencing (NGS). Next generation sequencing has excellent potential to flourish and increase the molecular applications in forensic sciences by jumping over the pitfalls of the conventional method of sequencing. The main advantages of NGS compared to conventional method that it utilizes simultaneously a large number of genetic markers with high-resolution of genetic data. These advantages will help in solving several challenges such as mixture analysis and dealing with minute degraded samples. Based on these new technologies, many markers could be examined to get important biological data such as age, geographical origins, tissue type determination, external visible traits and monozygotic twins identification. It also could get data related to microbes, insects, plants and soil which are of great medico-legal importance. Despite the dozens of forensic research involving NGS, there are requirements before using this technology routinely in forensic cases. Thus, there is a great need to more studies that address robustness of these techniques. Therefore, this work highlights the applications of forensic sciences in the era of massively parallel sequencing.